'Pyrococcus furiosus, 30 years on'. Issue 6 (20th February 2017) - Kengen, Servé W. M.
Abstract : Pyrococcus furiosus has come of age. In 1986 the first publication on a remarkable microorganism, Pyrococcus furiosus, appeared. Now, 30 years later it is still "the fast and the furious".